Bratteli-Vershik models for Cantor minimal systems associated to interval exchange transformations - Gjerde, Richard; Johansen, Ørjan (MATHEMATICA SCANDINAVICA, 2002)
We construct Bratteli-Vershik models for minimal interval exchange transformations. We use this to show that the interval exchange transformations over quadratic fields, recently studied by Boshernitzan and Carroll, actually are (conjugate to) substitution minimal systems. We also prove a partial converse to this. Furthermore, these systems are orbit equivalent to Sturmian systems.